2-Hydroxy-N-phenylbenzamides and Their Esters Inhibit Acetylcholinesterase and Butyrylcholinesterase - Martin Krátký; Šárka Štěpánková; Neto-Honorius Houngbedji; Rudolf Vosátka; Katarína Vorčáková; Jarmila Vinšová (Biomolecules, 2019)
The development of novel inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) represents a viable approach to alleviate Alzheimer’s disease. Thirty-six halogenated 2-hydroxy-N-phenylbenzamides (salicylanilides) with various substitution patterns and their esters with phosphorus-based acids were synthesized in yields of 72% to 92% and characterized. They were evaluated for in vitro inhibition of AChE from electric eel and BuChE from equine serum using modified Ellman’s spectrophotometric method. The benzamides exhibited a moderate inhibition of AChE with IC50 values in a narrow concentration range from 33.1 to 85.8 µM. IC50 values for BuChE were higher (53.5−228.4 µM). The majority of derivatives inhibit AChE more efficiently than BuChE and are comparable or superior to rivastigmine—an established cholinesterases inhibitor used in the treatment of Alzheimer’s disease. Phosphorus-based esters especially improved the activity against BuChE with 5-chloro-2-{[4-(trifluoromethyl)phenyl]carbamoyl}phenyl diethyl phosphite 5c superiority (IC50 = 2.4 µM). This derivative was also the most selective inhibitor of BuChE. It caused a mixed inhibition of both cholinesterases and acted as a pseudo-irreversible inhibitor. Several structure-activity relationships were identified, e.g., favouring esters and benzamides obtained from 5-halogenosalicylic acids and polyhalogenated anilines. Both 2-hydroxy-N-phenylbenzamides and esters share convenient physicochemical properties for blood-brain-barrier penetration and thus central nervous system delivery.